2009
DOI: 10.1186/1476-7120-7-15
|View full text |Cite
|
Sign up to set email alerts
|

Transesophageal echocardiography in patients with cryptogenic cerebral ischemia

Abstract: Background: In about one third of all patients with cerebral ischemia, no definite cause can be identified (cryptogenic stroke). In many patients with initially suspected cryptogenic stroke, however, a cardiogenic etiology can eventually be determined. Hence, the aim of this study was to describe the prevalence of abnormal echocardiographic findings in a large number of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 30 publications
(31 reference statements)
0
18
0
1
Order By: Relevance
“…It is noteworthy that LVDD is well established as a risk factor for incident AF. 9,13,[25][26][27][28] Many clinicians had assumed that LVDD is a physiological mechanism for how certain risk factors, such as hypertension, contribute to the development of AF. 13 AF may be related to the increased incidence of LVDD-related coexisting pathological changes in the myocardium and atrial tissue.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that LVDD is well established as a risk factor for incident AF. 9,13,[25][26][27][28] Many clinicians had assumed that LVDD is a physiological mechanism for how certain risk factors, such as hypertension, contribute to the development of AF. 13 AF may be related to the increased incidence of LVDD-related coexisting pathological changes in the myocardium and atrial tissue.…”
Section: Discussionmentioning
confidence: 99%
“…15 In another study, TEE identified a cardiac source in about 50% of patients when the basic evaluation including TTE failed to identify a source. In this study, a PFO was the most often detected potential cardiac source, followed by valvular abnormalities and aortic plaques.…”
Section: Cardiac Testingmentioning
confidence: 97%
“…18 Left atrial or left ventricular thrombus is identified in 1%-16% of patients with cryptogenic stroke, with TEE being more sensitive than TTE. 14,15 When found, this should prompt consideration of anticoagulation. Furthermore, when endocarditis is clinically suspected, TEE is more sensitive than TTE in identifying valvular vegetations, suggesting the need for IV antibiotics.…”
Section: Cardiac Testingmentioning
confidence: 99%
“…(16) TEE is thus recommended for all patients with cryptogenic stroke to identify PFO or other cardiac causes. (14,15) results oF trAnscAtheter closure In…”
Section: Pfo and Strokementioning
confidence: 99%
“…In patients with cryptogenic stroke, it is recommended that TEE should routinely be included in the assessment of such patients since it also allows other cardiovascular causes of stroke to be detected. (13)(14)(15) FIGure 2: tEE images of Pfo. In A, a long tunnel-like Pfo is demonstrated with a thin septum secundum overlapping (arrow) a thick septum secundum.…”
mentioning
confidence: 99%